2023
DOI: 10.1002/solr.202300156
|View full text |Cite
|
Sign up to set email alerts
|

Brief Outlook on Top Cell Absorber of Silicon‐Based Tandem Solar Cells

Abstract: Silicon (Si) is a low‐cost, stable photovoltaic market contributor which is approaching its single‐junction theoretical efficiency limit. To further elevate the efficiency of crystalline Si (c‐Si) afterward, Si solar cells (SCs) need a proper top cell absorber in Si tandem SCs. Herein, the top cell absorber is studied by evaluating their current state of the art, the existing challenges, and possible future solutions which can enhance their efficiency. The progress of perovskite/Si tandem SC both for monolithi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 220 publications
0
2
0
Order By: Relevance
“…随后, 中间带太阳能电池、热载流子太阳能电 池、多激子太阳能电池和叠层(串联)太阳能电池 等被人们提出并尝试超越单结太阳能电池SQ极 限 [14][15][16] , 获得更高效的太阳能电池. 其中叠层太阳 能电池被认为是最容易实现的选择, 且于1990年 开始在航空航天器件中使用 [17] .…”
unclassified
“…随后, 中间带太阳能电池、热载流子太阳能电 池、多激子太阳能电池和叠层(串联)太阳能电池 等被人们提出并尝试超越单结太阳能电池SQ极 限 [14][15][16] , 获得更高效的太阳能电池. 其中叠层太阳 能电池被认为是最容易实现的选择, 且于1990年 开始在航空航天器件中使用 [17] .…”
unclassified
“…Table 1 compiles a short list of published work on chalcogenide or chalcopyrite tandems. More detailed discussion can be found in reviews of the subject, for example [31,32] and [33].…”
Section: Research Directions Of Thin Film Tandem Absorber Candidates ...mentioning
confidence: 99%
“…Hence, it is necessary to have a tuneable bandgap in SiC materials. [13] Experimentally SiC can be synthesized by chemical vapor deposition (CVD), vapor liquid solid (VLS), and physical vapor transport (PVT). [14][15][16][17] It has been shown that the conversion efficiency of the nonstoichiometric S x iC 1-x -based p-n junction can be improved by varying the reactant fluence ratio (R) in plasma-enhanced chemical vapor deposition (PECVD).…”
Section: Introductionmentioning
confidence: 99%